A study on the impact of smartphone use on haematological and cardiovascular parameters in the adult population: A cross-sectional study. - Kumar, Samir; Dinkar, Jyoti Kumar; Priyanka; Kumar, Randhir; Shilpa, Shaily; Kumar, Satish (Student’s Journal of Health Research Africa, 2025)
Background The increasing use of mobile phones has raised concerns about their potential health effects, particularly on cardiovascular, inflammatory, and hematological parameters. This study investigates the impact of mobile phone usage on WBC count and blood pressure among adults. Methods This study was conducted at IGIMS, Patna, to assess the effects of mobile phone radiation on cardiovascular, inflammatory, and hematological parameters. Blood pressure was measured using a mercury sphygmomanometer, and the WBC count was analyzed using the hemocytometer method. Data on mobile phone usage were obtained from call logs, and statistical analysis was performed using SPSS with a significance level of p<0.05. Results The study included mostly males (86%) aged 21-25 years (76%). Blood pressure analysis revealed that 47% had systolic BP >120 mmHg, and 51% had diastolic BP >80 mmHg. No significant correlation was found between mobile phone usage and blood pressure or leukocyte count (p > 0.05). Overall, mobile phone use showed minimal impact on cardiovascular and hematological parameters, including total leukocyte count and CRP levels, in young adults at IGIMS, Patna. Conclusion Prolonged mobile phone use showed a non-significant trend toward higher blood pressure, but no direct impact on leukocyte count. Further studies with larger samples are needed to explore potential health effects. Recommendation Future studies should involve a larger and more diverse population to enhance the validity of the findings. Long-term monitoring of mobile phone usage and its health effects should also be explored.